Use of blend based on an emulsifier, monolaurin, and glycerides of butyric acid in the diet of broilers: Impacts on intestinal health, performance, and meat - Almeida A.B.* (2021)
© 2021, Academia Brasileira de Ciencias. All rights reserved.The objective of this study was to evaluate whether the addition of a blend based on α-monolaurin mono-, di-and triglycerides of butyric acid, and lysolecithin on the performance even on diets containing reduced inclusion of oil in the diet and without the use of growth-promoting antibiotics of broilers considering the effect on health, performance, and meat. Three treatments were defined: positive control (TP: with enramycin), negative control (TN: no enramycin), and blend (T-FRA: with monolaurin and glycerides of acid butyric minus 0.8% soybean oil). At 21 days, broilers treated with TP and T-FRA obtained the lower feed conversion ratio (FC); at 35 days, T-FRA broilers obtained lower FC than TN broilers. Cholesterol levels were higher in the blood of T-FRA broilers. On day 42, levels of ROS and TBARS were lower in the intestine, muscles, and liver of T-FRA broilers. Moreover, glutathione S-transferase and total non-enzymatic antioxidants were greater at the intestinal and muscular levels. The T-FRA broilers had a lower percentage of lipids in the meat. The MIC indicated that 111mg of the blend/ mL inhibited the growth of E. coli; however, the counts of total coliforms and E. coli in the feces and the broilers’ litter did not differ between treatments. In conclusion, the addition of the blend T-FRA in broiler diets was able to improve the feed conversion and maintain the other performance parameters even considering a reduction of 0.8% in the inclusion of oil.